Characterization and Comparative Analysis of Mitochondrial Genomes Among the Calliphoridae (Insecta: Diptera: Oestroidea) and Phylogenetic Implications - Shang, Yanjie; Ren, Lipin; Zhang, Xiangyan; Li, Yi; Zhang, Changquan; Guo, Yadong (Frontiers in Genetics, 2022)
The Calliphoridae (blowflies) are significant for forensic science, veterinary management, medical science and economic issues. However, the phylogenetic relationships within this family are poorly understood and controversial, and the status of the Calliphoridae has been the crucial problem for understanding the evolutionary relationships of the Oestroidea these years. In the present study, seven mitochondrial genomes (mitogenomes), including six calliphorid species and one Polleniidae species were sequenced and annotated. Then a comparative mitochondrial genomic analysis among the Calliphoridae is presented. Additionally, the phylogenetic relationship of the Calliphoridae within the larger context of the other Oestroidea was reconstructed based on the mitogenome datasets using maximum likelihood (ML) and Bayesian methods (BI). The results suggest the gene arrangement, codon usage and base composition are conserved within calliphorid species. The phylogenetic analysis based on the mitogenome dataset recovered the Calliphoridae as monophyletic and inferred the following topology within Oestroidea: (Oestridae (Sarcophagidae (Calliphoridae + (Polleniidae + (Mesembrinellidae + Tachinidae))))), although the number of exemplar species is limited, further studies are required. Within the Calliphoridae, the Chrysomyinae were recovered as sister taxon to Luciliinae + Calliphorinae. Our analyses indicated that mitogenomic data has the potential for illuminating the phylogenetic relationships in the Oestroidea as well as for the classification of the Calliphoridae.